In vivo Evaluation of Extracted and Fraction of Moringa oleifera leaves against Testosterone-Induced PCOS Model in Rattus Norvegicus - Widayatul Khairi; Nuraini Harmastuti; Gunawan Pamudji Widodo (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2023)
Background: Polycystic ovary syndrome (PCOS) is an endocrine disorder. Parameters characteristic of the disorder include weight gain, insulin resistance and malondialdehyde (MDA). The traditional medicine used is Moringa oleifera. Objectives: The aim was to determine the effect of weight loss and blood glucose levels, MDA levels and histopathological features of the ovarian follicles in the rat model PCOS-insulin resistance induced by testosterone. Methods: Extraction process, followed by fractionation using n-hexane, ethyl acetate and water, identification of compound content using TLC, and rats were grouped into 7 groups (n=5), namely normal group, negative group, positive group, extract, fraction water, ethyl acetate fraction and n-hexane fraction by looking at the characteristic parameters and ovarian histopathology. Data analysis using ANOVA and Kruskal-wallis. Results: The yield of the extract was 30.4%, the water fraction was 85.59%, the ethyl acetate fraction was 6.64% and the n-hexane fraction was 4.05%. Positive for flavonoids, tannins, alkaloids in the ethyl acetate fraction, the water and extract fractions were positive for tannins, the n-hexane fraction was positive for steroids. The modeling sample group obtained extract body weight 195.40 g, water fraction 195.80 g, ethyl acetate fraction 194.00 g, n-hexane fraction 196.00 g, blood glucose level extract 83.00 mg/dL, water fraction 84.27 mg/dL, ethyl acetate fraction 80.00 mg/dL, n-hexane fraction 122.85 mg/dL, MDA extract content 2.704 nmol/mL, water fraction 3.547 nmol/mL, 1.685 nmol/mL, 5.308 nmol /mL and can improve ovarian histopathology. Conclusion: The most effective value is the ethyl acetate fraction because it has the highest decrease in PCOS characteristics.